2016
DOI: 10.1111/ggi.12776
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactoferrin and lactoperoxidase‐containing food on the oral hygiene status of older individuals: A randomized, double blinded, placebo‐controlled clinical trial

Abstract: Lactoferrin and lactoperoxidase-containing tablet ingestion showed antibacterial effects on periodontal bacteria present in the tongue coating and supragingival plaque, indicating that long-term ingestion could improve the oral hygiene of older individuals. Geriatr Gerontol Int 2017; 17: 714-721.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 24 publications
(48 reference statements)
0
27
0
1
Order By: Relevance
“…In the present study, decreases in the total relative abundance of gram‐negative bacteria in supragingival plaque correlated with deterioration of oral health‐related variables, including O'Leary's PCR, BOP and total VSCs. In addition, at 8 weeks in the test group BOP had significantly decreased from baseline . These results suggest that the microbial shift induced by the test tablets from a gram‐negative‐dominant to a gram‐positive‐dominant community contributes to improvements in oral health.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In the present study, decreases in the total relative abundance of gram‐negative bacteria in supragingival plaque correlated with deterioration of oral health‐related variables, including O'Leary's PCR, BOP and total VSCs. In addition, at 8 weeks in the test group BOP had significantly decreased from baseline . These results suggest that the microbial shift induced by the test tablets from a gram‐negative‐dominant to a gram‐positive‐dominant community contributes to improvements in oral health.…”
Section: Discussionmentioning
confidence: 75%
“…The results of comparisons of the phylum composition suggest that ingestion of the test tablets does not markedly affect the overall structure of the microbiota in supragingival plaque and tongue coating. No adverse events related to the tablets were observed in any of the 46 study participants . Thus, long‐term use of the test tablets does not appear to result in microbial substitution.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Morita et al. () conducted a randomized, double‐blinded, placebo‐controlled clinical trial to investigate the effects of LF and lactoperoxidase (LPO)‐containing food on the oral hygiene status of a geriatric population. They found that ingestion of LF and LPO‐containing tablets for 8 weeks provided significant anti‐bacterial effects on the periodontal bacteria ( P. gingivalis and Fusobacterium nucleatum ) present in the tongue coating and supragingival plaque.…”
Section: Effect Of Lf On Periodontal Pathogensmentioning
confidence: 99%
“…No adverse events related to the test tablets were observed in any of the participants during the study period, consistent with the results of previous clinical studies. 17,29 Therefore, the LF and LPO-containing tablets investigated in this clinical trial may be safely used on a daily basis to maintain oral health.…”
Section: Discussionmentioning
confidence: 99%